ON THE DATE OF THE OLBIAN CALENDAR GRAFFITO SEG 30: 977 (JOURNAL OF ANCIENT HISTORY AND ARCHAEOLOGY, 2022)
The inscription SEG 30: 977, known as the calendar graffito, is one of the most interesting documents from Olbia and attracts scholarly attention for more than forty years. It contains a dedication to the god Apollo with several epicleseis, and a list of the twelve months, identical to the calendar of the Olbian metropolis Miletos, but for the spelling of several months’ names. The list of Apollo’s epicleseis, as well as such a list of the months, are unique in Greek epigraphy. Calendar inscriptions are common since the 4th century BCE, but the Olbian inscription is traditionally dated to the second quarter of the 5th century BCE, and therefore considered as the earliest calendar inscription in the Greek world. This date is however incorrect and should be moved to the beginning of the 4th century, on the basis of the script and spelling of the graffito, as well as the form of vessel.